Emission Reduction Study for Eco-Campus Program, Case Study in Sepuluh Nopember Institute of Technology Indonesia - Ridho Hantoro; Detak Yan Pratama; Endah Laksmi Nugraha; Rizky Nanda Puspitasari (IPTEK Journal of Proceedings Series, 2017)
Emission of CO2 in Indonesia is high relatively and have reached 1,55-ton carbon (5,67 ton CO2 – eq) per capita. It is predicted to increase up to 3,22-ton carbon per capita in 2050 as increasing of population growth. Indonesian Government has issued the policy for decreasing greenhouse gasses effect below 26% in 2020. It proposed to all of society not only public and private institutions, but also education institution like campus. This study is aimed to identify the factors which can influence greenhouse gasses effect, including carbon emission in transportation, waste management and electrical consumption in Sepuluh Nopember Institute of Technology (ITS). It is projected to support implementation of ITS eco campus program more effectively. Therefore, this study has formulated local planning and policy which can be implemented by campus community to decrease carbon emission and organize ITS as real eco-campus.